Beginning iOS apps with Facebook and Twitter APIs for iPhone, iPad, and iPod touch - Dannen, Chris (Apress, 2011)
Beginning iOS Apps with Facebook and Twitter APIs shows you how to add the power of social networking to your mobile apps on iPhone, iPad, and iPod touch. With this book as your guide, you can write apps that connect to Facebook and Twitter quickly, securely, and discreetly. Instead of starting from scratch, you will build on the vast resources, data storage capacity, and familiar features of these platforms which have become part of everyday life for hundreds of millions of users worldwide. Beginning iOS Apps with Facebook and Twitter APIs introduces you to the development tools, techniques, and design practices you will need to work with the APIs. It helps you decide whether to use Facebook, Twitter, or both, and explains the important issues of design, branding, and permissible use guidelines. You will learn how to guarantee privacy and use OAuth for authentication and single sign-on. Create news apps, shopping apps, contact apps, GPS apps, guides, and more, that let users transparently: Sign on once, then freely work with and manage their Facebook and Twitter accounts; Publish game high scores, post likes, links, and status updates; Send messages, share pictures, and forward Tweets; Tweet a link to an event, show themselves as attending, and see who else is there; Show Tweets that are relevant to a topic within a news app; Show Tweets about a restaurant; Organize a group or community. From time to time, new forms of communication come along that make it easier for people to communicate and manage their social lives. Like phone calls and SMS before them, Facebook and Twitter have, in a short time, become essential parts of the social fabric of life for an ever-growing number of people throughout the world. The knowledge you'll gain from Beginning iOS Apps with Facebook and Twitter APIs will help you create exciting and popular iOS apps that your users will rely on every day to help make their lives more meaningful and connected.